Can Biomass Energy Be a Potential for Rural Development? A Roadmap for Karacabey (Bursa) - Balci, Pinar; Evren, Yigit (KARE PUBL, 2015)
The importance given to renewable energy has been gradually increasing as it helps countries to reduce environmental pollution and their dependence on foreign energy. Raw materials used in biomass renewable energy are mainly obtained from the implementation of energy agriculture. In this way; local resources are used for the production of environment-friendly renewable energy, agricultural activities are stimulated and thus rural development can be reinforced in less developed peripheral regions. The aim of this study is to investigate the relationship between biomass energy, energy agriculture and rural development in Karacabey. For this purpose, the potentials of this rural region are studied and a road map for local development is presented.
Keywords: Renewable energy; biomass energy; energy agriculture; rural development; Public Administration